1990
DOI: 10.1093/oxfordjournals.humrep.a137224
|View full text |Cite
|
Sign up to set email alerts
|

Liver abnormality in ovarian hyperstimulation syndrome

Abstract: Ovarian hyperstimulation syndrome (OHSS) is a potentially fatal condition associated with the therapeutic induction of ovulation in infertility. Liver function abnormality has been previously reported in four patients, one of whom had ultrastructural abnormalities on liver biopsy. This paper describes a patient presenting with severe OHSS 16 days after ovulation had been induced. Liver function abnormality was apparent 11 days later, with a sustained rise in alkaline phosphatase and aspartate aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Borgaonkar and Marshall reported a marked increase of aminotransferases in association with OHSS: after 23 days from induction of ovulation, their patient developed ascites and pleural effusion; aminotransferases reached values of ALT 1472 IU/L and AST 908 IU/L 4 days following stimulation; ALP and GGT reached 186 and 908 IU/L, respectively, while serum bilirubin was normal. Ryley et al . described a patient suffering from severe OHSS, who showed a sustained increase of aminotransferases persisting at high levels for a period of 2 months; enzymatic abnormalities were associated with several histologic (zonal fatty degeneration and inflammation) and cytological (mitochondrial crystalline inclusions and dilated endoplasmic reticulum) alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borgaonkar and Marshall reported a marked increase of aminotransferases in association with OHSS: after 23 days from induction of ovulation, their patient developed ascites and pleural effusion; aminotransferases reached values of ALT 1472 IU/L and AST 908 IU/L 4 days following stimulation; ALP and GGT reached 186 and 908 IU/L, respectively, while serum bilirubin was normal. Ryley et al . described a patient suffering from severe OHSS, who showed a sustained increase of aminotransferases persisting at high levels for a period of 2 months; enzymatic abnormalities were associated with several histologic (zonal fatty degeneration and inflammation) and cytological (mitochondrial crystalline inclusions and dilated endoplasmic reticulum) alterations.…”
Section: Discussionmentioning
confidence: 99%
“…According to our case, several evidences documented possible alterations of liver enzymes because of an unopposed ovarian hormonal overproduction. Hepatic alterations included a very wide spectrum of severity varying from mild–moderate forms to more severe ones . According to Delvigne and Rozenberg, oestrogens probably cause microvascular alterations such as vasodilatation, increased vascular permeability and consequent hepatocyte swelling, to which follows an amplified cellular permeability with consequent release of AST and ALT; alternatively, the estrogen‐induced production of mediators such as IL‐6 may cause microvascular thromboses and hepatic ischemia .…”
Section: Discussionmentioning
confidence: 99%
“…Autopsies performed on patients who died from OHSS showed interesting hepatic histological lesions. Ryley et al [8] showed the presence of macrovesicular steatosis involving the periportal areas with an inflammatory infiltrate composed mainly of mononuclear cells and marked Kupffer cell hyperplasia. Electron microscopic ultrastructural examination of hepatocytes disclosed the presence of mitochondrial crystalline inclusions and dilatation of the rough endoplasmic reticulum, similar to that observed occasionally in pregnancy or during administration of oral contraceptives or anabolic steroids [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the most severe form or critical OHSS may develop hypovolemic shock, 10 pleural effusions, 9 ARDS, 13 liver dysfunction, 12 a decline in renal function, 11 thrombotic events, [14][15][16] and even death. 17 A massive leukocytosis is often seen in these patients.…”
Section: Treatmentmentioning
confidence: 99%